1989
DOI: 10.1128/jvi.63.9.3714-3728.1989
|View full text |Cite
|
Sign up to set email alerts
|

Separation of primary structural components conferring autoregulation, transactivation, and DNA-binding properties to the herpes simplex virus transcriptional regulatory protein ICP4

Abstract: A truncated ICP4 peptide which contains the amino-terminal 774 amino acids of the 1,298-amino-acid polypeptide is proficient for DNA binding, autoregulation, and transactivation of some viral genes (N. A. DeLuca and P. A. Schaffer, J. Virol. 62:732-743, 1988) and hence exhibits many of the properties characteristic of intact ICP4. To define the primary sequence important for the activities inherent in the amino-terminal half of the ICP4 molecule, insertional and deletion mutagenesis of the sequences encoding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
109
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 52 publications
8
109
0
Order By: Relevance
“…Previous studies have demonstrated that deletion of the conserved serine-rich sequence in the background of an ICP4 polypeptide truncated at residue 774 resulted in a loss of the ability to transactivate the early thymidine kinase gene promoter in transient assays (57). Paterson and Everett have also investigated the effect of mutations in the serine-rich region on the function of ICP4.…”
Section: Growth Properties Of Mutant Viruses Lacking the Serine-rich mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that deletion of the conserved serine-rich sequence in the background of an ICP4 polypeptide truncated at residue 774 resulted in a loss of the ability to transactivate the early thymidine kinase gene promoter in transient assays (57). Paterson and Everett have also investigated the effect of mutations in the serine-rich region on the function of ICP4.…”
Section: Growth Properties Of Mutant Viruses Lacking the Serine-rich mentioning
confidence: 99%
“…Clustered regions in the ICP4 primary structure are conserved among the ICP4 homologs of related alphaherpesviruses (4,21,37,60), suggesting the presence of functionally important domains. Genetic analysis of mutant ICP4 polypeptides has identified several such regions of conserved primary sequence that are required for the ICP4 regulatory activities (11,43,57). One of these regions, between amino acid residues 263 and 487, specifies the primary structure important for ICP4 DNA-binding activity (42,57).…”
mentioning
confidence: 99%
See 3 more Smart Citations